Modeling and empirical evidence of the impact of implementation of sugar sweetened-beverages tax to reduce non-communicable diseases prevalence: a systematic review - Firdaus, Safira; Andarwulan, Nuri; Hariyadi, Purwiyatno (Frontiers in Nutrition, 2024)
Introduction The surge in non-communicable diseases (NCDs) has been linked to excessive sugar-sweetened beverage (SSB) consumption. In response, the World Health Organization advocates for SSB taxes as a preventive measure. This study conducts a systematic literature review, encompassing simulation modeling and empirical evidence, to evaluate the effectiveness of SSB taxes in diminishing NCD prevalence. Method A systematic search from August 2002 to August 2022, utilizing databases like ScienceDirect, PubMed, Google Scholar, Wiley Online Library, Springer, and ResearchGate, identified 29 relevant articles worldwide following PRISMA 2020. The Critical Appraisal Skill Programme (CASP) 2018 tool was employed for economic evaluation Result Among the selected articles, 22 utilized simulation models in group of countries such as South Africa, the US, the UK, Asia (Philippines, India, Indonesia, Thailand), Australia, and Europe (Germany), while seven were based on US and UK evidence. Simulation modeling consistently demonstrated that SSB taxes significantly reduced NCD incidence, prevalence, and mortality, also bolstering government revenue. Tax rates in simulations ranged from 10 to 25%. However, empirical evidence indicated a limited impact, primarily due to low tax rates. Notably, a UK-specific tax led to a 2.7% reduction in SSB sugar purchases and 40.2% higher purchases of no-levy drinks. Discussion The findings suggest that while simulation models demonstrate the potential effectiveness of SSB taxes in reducing NCDs, empirical evidence reveals there is no significant effect of the SSB tax, Based on the study conducted in this study, the SSB tax is not effective in reducing the prevalence of NCDs due to consumer preferences that have not changed. , likely due to the implementation of lower tax rates and failure to fulfill the assumption of subtitution product, physical activity, and so on. The study highlights that SSB tax is not effective in reducing the prevalence of NCDs due to consumer preference that have not change. Multi-actions are needed to support the sustainability of the implementation of the SSB tax, including education and promotion of healthy lifestyles and encouragement to reformulate SSB products by industry.